Clinical Manifestations, Microbial Agents, and Types of Infection in Children With Urinary Tract Infection: Urinary Tract Infection in Children - Naseri, Mitra; Aghatabi, Elham; Tafazoli, Niayesh; Tafazoli, Nooshin (Journal of Pediatric Nephrology, 2022)
Background and Aim: Urinary Tract Infection (UTI) is common in children. This study aims to evaluate demographic characteristics, etiologies, and clinical presentations of UTI in childhood. Methods: A cross-sectional retrospective study was conducted to investigate the available data of the children with UTI referred to the nephrology clinic of a tertiary academic children’s hospital from September 2002- 2016. Patients aged 0-18 years were included in the study. Results: A total of 1245 cases, including 1084 girls (87.06%) and 161 boys (12.94%) were included in the study. The age of patients at the first presentation was 35.43±34.94 months. Fever was the most common manifestation (60.1%). The most and least cases of UTI were reported in children aged 2-24 months (49.7%) and over 10 years old (2.9%), respectively. The most common pathogens were E. coli, Klebsiella, Staphylococcus, Enterobacter, Proteus, and Enterococcus species, respectively. The frequency of infection with E. coli in girls was significantly higher than in boys (P=0001), while infection with Staphylococcus and Proteus species was higher in boys (P=0.0001 and 0.002, respectively). The incidence of pyelonephritis decreased with age. Furthermore, febrile UTIs were as common in boys as in girls (P=0.42). Conclusion: The prevalence of UTI is significantly higher in girls, and the frequency of UTI varies according to age, reaching its peak in the first year of life, and the lowest frequency in children over 10 years of age. Moreover, pyelonephritis is more common in younger children (infants 2-24 months). Gender is a crucial factor in terms of pathogens.